Relationship Between Religious Beliefs and Professional Ethics with the Mediating Role of Spiritual Intelligence and School Ethical Climate Among Male Secondary School Teachers in Jahrom - Karimi Dashtaki, Ahmad; Mahmoudi, Mohammad; Pourqardash Derazi, Najmeh (Assessment and Practice in Educational Sciences, 2026)
The present study aimed to examine the relationship between religious beliefs and professional ethics with the mediating role of spiritual intelligence and school ethical climate among male secondary school teachers in Jahrom. In terms of purpose, this study was applied research. Furthermore, it was a descriptive-correlational study employing a structural equation modeling approach. Regarding the method of data collection, the study was classified as field research. The statistical population included all male secondary school teachers in Jahrom, comprising 470 teachers across 31 male secondary schools. Based on the Morgan Table, a sample size of 211 participants was selected. Data collection instruments included the Professional Ethics Questionnaire developed by Ghasemzadeh (2014), the Islamic Religiosity Questionnaire developed by Safdel (2014), the Spiritual Intelligence Questionnaire developed by Farhoush (2019), and the Ethical Climate Questionnaire developed by Victor and Cullen (1988). After analyzing the research data using SmartPLS version 3.5, the results indicated that the mediating role of ethical climate in the relationship between religious beliefs and professional ethics was confirmed with a coefficient of 0.213 (p < .05). However, the mediating role of spiritual intelligence in the relationship between religious beliefs and professional ethics was rejected (p > .05). The relationship between religious beliefs and professional ethics was confirmed with a coefficient of 0.362 (p < .05). The relationship between religious beliefs and ethical climate was confirmed with a coefficient of 0.356 (p < .05). The relationship between religious beliefs and spiritual intelligence was confirmed with a coefficient of 0.717 (p < .05). In addition, the relationship between ethical climate and professional ethics was confirmed with a coefficient of 0.599 (p < .05). The findings of this study emphasize that teachers’ religious beliefs and the ethical climate of the educational environment have a significant impact on teachers’ professional ethics. Therefore, strengthening these factors may contribute to improving teachers’ ethical performance and ultimately enhancing the quality of education.